Barbados : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Barbados' deficit declined to 4.4 percent of GDP in 2016, about of half that in 2014, owing to lower energy prices and a recovery in export earnings. The current account deficit is projected to continue to narrow to 3.7 percent in 2017, and to 2.9 percent of GDP in 2018 as a result of lower imports, but continued weakness in the financial account and delayed privatization will contribute to weak reserves. The fiscal deficit is estimated to have declined to 5.5 percent of GDP in FY2016/17. The IMF staff project further progress in reducing the fiscal deficit, to 4.1 percent of GDP in FY2017/18 without divestment proceeds.